2020
DOI: 10.1371/journal.pone.0238438
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio cholerae isolates from freshwater sources in northwest Ohio

Abstract: Vibrio cholerae is a natural inhabitant of aquatic ecosystems worldwide, typically residing in coastal or brackish water. While more than 200 serogroups have been identified, only serogroups O1 and O139 have been associated with epidemic cholera. However, infections other than cholera can be caused by nonepidemic, non-O1/non-O139 V. cholerae strains, including gastroenteritis and extraintestinal infections. While V. cholerae can also survive in freshwater, that is typically only observed in regions of the worl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…As this organism is generally a pathogen found in more tropical regions near the ocean, literature was again reviewed to determine if there was precedence for V. cholerae in Ohio. Indeed, V. cholerae isolates have been found in freshwater sources in northwest Ohio ( 31 ). While these strains are not from the serogroups (O1 and O139) that cause epidemic cholera, the isolates characterized in Daboul et al contained a variety of virulence genes that could cause gastroenteritis or other human infections.…”
Section: Resultsmentioning
confidence: 99%
“…As this organism is generally a pathogen found in more tropical regions near the ocean, literature was again reviewed to determine if there was precedence for V. cholerae in Ohio. Indeed, V. cholerae isolates have been found in freshwater sources in northwest Ohio ( 31 ). While these strains are not from the serogroups (O1 and O139) that cause epidemic cholera, the isolates characterized in Daboul et al contained a variety of virulence genes that could cause gastroenteritis or other human infections.…”
Section: Resultsmentioning
confidence: 99%
“…Vibrio spp. presence is not commonly studied in non-coastal areas of the United States; however, a recent study isolated Vibrio cholerae from lakes and rivers in northwest Ohio, with several isolates showing resistance to antibiotics . Vibrio organisms have been isolated in 75–100% of MWWTF effluents sampled in South Africa, Italy, and France. ,, Species of Mycobacterium spp., such as M.…”
Section: Resultsmentioning
confidence: 99%
“…Vibrio cholerae widely exists in all types of waterbodies [ 19 , 20 ] and it has been reported that V. cholerae can infect aquatic animals including fish [ 21 , 22 ], shrimps [ 23 , 24 ] and other aquaculture animals [ 25 , 26 ]. The cause of cholera epidemics is extraordinarily complex, and it is unclear how it spreads, while the reason for seasonal epidemic peaks in epidemic areas are also unknown.…”
Section: Discussionmentioning
confidence: 99%